Qur’anic Learning Management in Pesantren: Navigating the Tension Between Tradition and Innovation - Syah, Rio Febrian; Yunus, Moch; Herwati, Herwati (Journal of Educational Management Research, 2025)
Indonesian pesantren play a pivotal role in Islamic education, particularly in shaping the moral and spiritual character of the younger generation. Amid rapid modernization and technological advancement, pesantren are challenged to remain relevant while preserving their traditional values. This study examines the Qur’anic learning model at Pondok Pesantren Zainul Hasan Genggong, which integrates classical methods such as bandongan, sorogan, and wetonan with innovative, technology-based approaches. Employing a descriptive qualitative method, data were collected through observations, in-depth interviews, and documentation involving teachers and students. Findings reveal that the synergy between tradition and innovation enhances the quality of Qur’anic instruction, broadens access to global Islamic scholarship, and strengthens students’ moral and spiritual foundations. From a management perspective, this integration demonstrates how adaptive leadership, resource optimization, and strategic curriculum design can preserve institutional identity while fostering innovation. The model offers a replicable framework for developing holistic, context-sensitive Islamic education systems capable of navigating both heritage preservation and future readiness.